If it's not what You are looking for type in the equation solver your own equation and let us solve it.
k in (-oo:+oo)
6*k-6 = 3*k+3 // - 3*k+3
6*k-(3*k)-6-3 = 0
6*k-3*k-6-3 = 0
3*k-9 = 0 // + 9
3*k = 9 // : 3
k = 9/3
k = 3
k = 3
| 4a+10=7a-2 | | 5-4k=5k+50 | | -4t+2=112+6t | | -2+t=2t-1 | | 5x+2=2x+26 | | -8+2m=-2m+12 | | x+4=6x+4 | | 7+6k=-7k+7 | | 2m+2=-7m+56 | | 3a+3=-5a-37 | | 10-4t=-3t+1 | | 2b-1=-b+29 | | 2w-3=-12+5w | | 9+x=5x-19 | | 10-7k=3k+10 | | -2t+2=7t-16 | | (3/8)/100 | | 6n-7=5n-3 | | -7+7a=-4a-106 | | -3m+2=m-2 | | 3/8/100 | | -8-7t=-4t-44 | | 5-n=2n+17 | | 10+7n=6n+14 | | 4m+8=6m-4 | | 4d+10=-38-2d | | -1-2b=-6b-21 | | -4a+4=6a-86 | | 3+5n=-5n+3 | | 1+4x=7x-26 | | 7m-9=m-57 | | 3t+10=-100-7t |